Evaluation of Drug Storage at the Pharmaceutical Installation of Mutiara Cikutra Clinic Bandung for the Period of May 2025 – June 2025 - Avizza, Pinkan Ledy; Rosmiati , Meiti; sari, kartika (Journal of Scientific Insights, 2025)
Drug storage is a crucial component of pharmaceutical services aimed at maintaining the quality, stability, and safety of medications until they are administered to patients. This study aimed to evaluate the compliance of drug storage practices at the Pharmacy Installation of Mutiara Cikutra Clinic Bandung with the standards set by the Indonesian Ministry of Health Regulation No. 34 of 2021. The research was conducted from May to June 2025 using a descriptive qualitative approach through direct observation, in-depth interviews, and documentation. The results showed a compliance rate of 90,48% (19 out of 21 variables met the criteria). Overall, the storage system adhered to Good Storage Practice (GSP) principles, including proper arrangement based on dosage forms, temperature and humidity monitoring, and implementation of FIFO/FEFO systems. However, the study identified weaknesses in storage location vulnerability to flooding and the lack of physical separation for high alert medications. These findings underscore the need to strengthen SOPs, provide routine staff training, and implement risk-based digital monitoring systems to enhance the quality of pharmaceutical services in the clinic.